Assessing the Need for Anti-Doping Education: A Study among Athletes - Amatya, Diwakar Lal (Mangal Research Journal, 2023)
The present study aims to assess the level of awareness and knowledge among athletes regarding anti-doping education. Population of the study was 102 Nepalese athletes who participated in different South Asian Games held until 2019. The participants of this study were the athletes selected from sports disciplines that were entertained in the 13th South Asian Federation Games held in Kathmandu/Pokhara/ Janakpur and earlier. This study employed non-probability sampling method to select the athletes who were interviewed on their knowledge and education on doping. This study used a mixed-methods research design which employed quantitative data analysis techniques to identify patterns and trends in athletes' responses and qualitative to explore athletes' experiences, attitudes, and perceptions to gain qualitative insights into the need for anti-doping education. Moreover, this study employed interview as a tool of data collection and descriptive method used to analyse data. It used statistical graphic techniques to present information about data such as pie charts, bar-diagrams and simple percentage to analyze the data. It is revealed that one third of the athletes are found to ignore the effect of coffee and taking drug and the cough syrup could cause them into trouble of doping. Also, higher number of athletes did have not knowledge on side effects of anabolic androgenic steroids. Surprisingly, one fourth of athletes used to take diuretics for the reduction of the body weight before competition. The findings suggest that the level of awareness and knowledge regarding anti-doping is limited in Nepalese athletes. Based on the results of the study, the athletes should be provided anti-doping education properly in order to prevent trouble of doping in the athletes.